Evaluación del riesgo y reincidencia en agresores sexuales sentenciados: implicaciones para las víctimas (2010)
The study of the occurrence of the sexual crimes has a tripartite implication in which there are interfered elements that interact quite frequently, and occasionally in a disadvantageous way. On one hand, the recovery and repair of the victim, as the recipient of the damage, is considered; and on the other, the treatment of and the criminal proceedings against the aggressor; and finally, the processes of regulation and imparting of the Penal System in its attempt for representing the regulatory mechanism which restores the repercussions created by the aggression. Complexes are both, crimes, as well as the discussion about the balance needed by the rehabilitation to avoid the re-victimization. The paper describes empirically the profiles of inmates in Spanish and Mexican penitentiary system. It analyses their implication for repetition or for victim risk. It emphasizes the diagnosis in the criminological area as a fundamental tool. This tool needs of specific, valid and reliable evaluation means to having real approximations about the personal disposition to commit antisocial behaviors, which is relevant not only from a criminal politics perspective, with the goal of the psychological study in aggressors, study that among others could contribute to the safety of victims.